Rapid detection of mobile resistance genes tetA and tetB from metaplasmid isolated from healthy broiler feces. (May 2022) - Sreejith, S.; Shajahan, Shamna; Prathiush, P.R.; Anjana, V.M.; Mathew, Jyothis; Aparna, S.; Abraham, Swapna Susan; Radhakrishnan, E.K.
Abstract: Containing antimicrobial resistance is the thought of the moment as it affects the human life from every aspect. Because, the inappropriate use of antibiotics in livestock animals for the growth promotion and prophylactic purpose has already generated significant challenges. The livestock farms which harbor and disseminate drug resistant microorganisms have already been identified as potential source of resistance genes acquired by the sensitive strains. Hence there is high demand for the affordable and effective surveillance method for the detection of antimicrobial resistance genes from livestock. In this study, direct detection of antibiotic resistance from metaplasmid DNA isolated from the poultry feces was conducted. For the initial standardization, plasmid DNA purified from the previously characterized Escherichia coli and Klebsiella pneumoniae were used. The tet A and tet B genes amplified from the purified plasmid DNA were further confirmed by agarose gel electrophoresis and sequencing. Further to this, metaplasmid DNA was purified from 29 different poultry fecal samples and these were further screened for the presence of resistance genes. Among the 29 metaplasmid samples, 8 were positive for tet A gene and 9 were positive for tet B gene. The results of the study indicate the potential of PCR based methods for the rapid screening of poultry samples for the antibiotic stewardship in the livestock sector. Highlights: Metaplasmids from the healthy broiler feces have been isolated. Mobile AMR genes such as tet A and tet B have been detected using PCR. The technique can be used for the surveillance of AMR in livestock sector.